Pemberian Pupuk Silika Cair untuk Meningkatkan Pertumbuhan, Hasil, dan Toleransi Kekeringan Padi Sawah - ,, Sugiyanta; Dharmika, I Made; Siti Mulyani, dan Dedeh (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
As one of the silica (Si) accumulator, rice (Oryza sativa L.) requires large amounts of silica for growth. This study aimed to determine the effect of liquid silica fertilizer application on lowland rice growth and yield, and its roles in drought stress responses. The experiments were conducted at Sawah Baru rice field and Cikabayan Greenhouse Experiment Station, IPB, Bogor during the period of January to May 2016. The field experiment was set up in a randomized complete block design with 7 treatments and three replications. The greenhouses experiment was arranged in a split-plot randomized block design with 3 replications. The main plots were 5 levels of liquid silica fertilizer application, while the subplot was 5 level of various soil water contents. The results of the field experiment showed that the application of liquid silica fertilizer increased rice shoot dry weight, total and productive tiller numbers, and yield per plant, but did not increase yield per hectare. Meanwhile at greenhouse experiment, it showed that the use of liquid silica fertilizer reduced the number of rice stomata, but did not increase cuticle thickness and grain yield per plant. Silica application was not effective to alter drought in rice.